Mobile applications in radiation oncology: current choices and future potentials - Janssen, Stefan Ingo; El-Shafie, Rami; Ruder, Arne Mathias; Bürgy, Daniel; Scafa, Davide; Giordano, Frank Anton; Nicolay, Nils; Vogel, Marco M. E.; Combs, Stephanie; Fahlbusch, Fabian B.; Rades, Dirk; Käsmann, Lukas Tobias (Strahlentherapie und Onkologie, 2023)
To review existing scientific literature on mobile applications (apps) in the field of radiation oncology and to evaluate characteristics of commercially available apps across different platforms.